2023
DOI: 10.1038/s41467-023-38545-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-wavelength shifting in two-dimensional perovskite for sensitive and fast gamma-ray detection

Abstract: Lead halide perovskites have recently emerged as promising X/γ-ray scintillators. However, the small Stokes shift of exciton luminescence in perovskite scintillators creates problems for the light extraction efficiency and severely impedes their applications in hard X/γ-ray detection. Dopants have been used to shift the emission wavelength, but the radioluminescence lifetime has also been unwantedly extended. Herein, we demonstrate the intrinsic strain in 2D perovskite crystals as a general phenomenon, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…Radiation detection to convert high-energy photons into low-energy photons has received extensive attention in medical diagnostic technology, safety detection, computer tomography, etc. The mainstream indirect conversion method is to convert X-rays into light by using scintillators . However, commercial scintillators face the problems of a complicated preparation process with high-temperature crystallization above 1700 °C, which squeezes the area of the application of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation detection to convert high-energy photons into low-energy photons has received extensive attention in medical diagnostic technology, safety detection, computer tomography, etc. The mainstream indirect conversion method is to convert X-rays into light by using scintillators . However, commercial scintillators face the problems of a complicated preparation process with high-temperature crystallization above 1700 °C, which squeezes the area of the application of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Scintillator-based X-ray detectors play an essential role in medical diagnostics, industrial inspection, nuclear physics, and scientific research. As the core of the X-ray detector, an applied scintillator should have a good ability to absorb high-energy rays, such as X-rays, aiming to increase the deposition energy in the conversion phase, and exhibit an excellent band gap value to enhance the probability of electron–hole pair generation and improve the light yield. Generally, criteria for evaluating scintillators are usually based on the following parameters: light yield, decay time, resistance to irradiation damage, sensitivity and detection limit. Typical scintillating materials that have been reported include NaI/Tl, CsI/Tl, BaF 2 , LaBr 3 /Ce, CdWO 4 , Bi 4 Ge 3 O 12 (BGO), and LYSO/Ce . However, these materials, although widely studied for certain outstanding properties, are accompanied by unavoidable drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Jin et al showed an ER at 662 keV of 21.7% and a decay constant of 7.9 ns for (PEA) 2 PbBr 4 single crystals by suppressing the nonradiative defects in crystal growth. 9 Xie et al used lithium doping in (BA) 2 PbBr 4 single crystals and pushed the ER to 8% with a scintillation decay constant of 10.9 ns. 8 However, these 2D HOIP crystals favor in-plane growth, and thus, the crystal thickness is usually restricted to only a few millimeters, which is rather small to attenuate high energy gamma photons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent material progress has shown promise to overcome these challenges. Two categories of single crystals have been developed, namely, two-dimensional hybrid organic–inorganic perovskite (HOIPs) crystals and self-trapped exciton (STE) crystals. , Jin et al showed an ER at 662 keV of 21.7% and a decay constant of 7.9 ns for (PEA) 2 PbBr 4 single crystals by suppressing the nonradiative defects in crystal growth . Xie et al used lithium doping in (BA) 2 PbBr 4 single crystals and pushed the ER to 8% with a scintillation decay constant of 10.9 ns .…”
Section: Introductionmentioning
confidence: 99%